The school practitioner's concise companion to preventing violence and conflict - Franklin, Cynthia (Oxford University Press, 2008)
Evidence-based violence prevention programs and best implementation practices / Ron Avi Astor ... [et al.] -- Creating a violence-free school climate/culture / Mark Mattaini -- Assessing and predicting risk of violence : empirically-based methods / Gary Bowen -- Bullying : best practices for prevention and intervention in schools / Esther Howe, Elayne Haymes, Tanya Tenor -- An evidence-based approach to management of students who wish to harm others / James K. Nash -- Peer conflict : effective resolution strategies / Debra J. Woody -- Using social and emotional learning to address conflicts in the classroom / Jacqueline A. Norris -- Acquaintance sexual assault and sexual harassment among teens / Erin A. Casey, Paula S. Nurius -- Enhancing conflict resolution through family and school staff alliances : planning for parent/guardian participation in conferences / Martha J. Markward -- Engaging adolescents in prevention of sexual assault and harassment / Erin A Casey, Paula S. Nurius -- Effective interventions with dating violence and domestic violence / Beverly M. Black, Arlene N. Weisz -- Effective intervention with gangs and gang members / Timotea M. Elizalde, Gilbert A. Ramirez